2020
DOI: 10.3390/sym12071161
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Production Programming to Systematic Sorting and Remanufacturing in Second-Hand Clothing Recycling Industry

Abstract: This study proposes a multi-objective production programming model which is established for systematic sorting and remanufacturing second-hand clothes and the objectives are twofold: (1) minimizing the remanufacturing cost to maintain the competitiveness of second-hand clothing industry and (2) maximizing the recycle rate to reduce the environmental impact from the disposed clothes. Previous studies are lacking to involve the features of second-hand clothing recycled from reuse to recycle in optimizing both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The determination of DM's weight is an important work in the evaluation process. Therefore, we express the importance of DMs by PyFN and assume that PyFN (M ξ , N ξ ) is applied to the importance evaluation of the ξ-th DM, the weight of the DM is obtained from Equation (10).…”
Section: The Cocoso-d Methods For Magdm Problems With Pyfnsmentioning
confidence: 99%
See 2 more Smart Citations
“…The determination of DM's weight is an important work in the evaluation process. Therefore, we express the importance of DMs by PyFN and assume that PyFN (M ξ , N ξ ) is applied to the importance evaluation of the ξ-th DM, the weight of the DM is obtained from Equation (10).…”
Section: The Cocoso-d Methods For Magdm Problems With Pyfnsmentioning
confidence: 99%
“…These DMs, including a purchasing manager (e 1 ), a production manager (e 2 ), a consulting agency director (e 3 ) and industry association experts (e 4 ), are competent in decision-making and have nearly ten years of industry experience. The PyFN is expressed for the importance of DMs based on their educational background, knowledge structure, professional level and working time in the industry, and the weight of DMs is calculated according to Equation (10), as shown in Table 2. The four DMs evaluated the five WCRC alternatives with regard to six attributes, including recovery size (Y 1 ), recovery convenience (Y 2 ), recovery efficiency (Y 3 ), consumer satisfaction (Y 4 ), recovery cost (Y 5 ) and risk bearing (Y 6 ).…”
Section: Case Study: Wcrc Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results indicated that sorting by category maximizes the recycling rate. Remanufacturing costs are minimized by sorting by worn-out condition [58].…”
Section: Sortingmentioning
confidence: 99%
“…First, to identify the physical, usage, and technological conditions of incoming cores, where they are sorted by their quality level before any remanufacturing processes. Second, sorting operations represent an immediate solution to mitigating quality uncertainty in the core acquisition [7][8][9].…”
Section: Introductionmentioning
confidence: 99%